The Effect of Remote Working Fatigue on Turnover Intentions Among Millennial Employees in the Post-Pandemic Workplace - Syakir, Adam; Hasna, Qaisara; Mawiza, Mawiza (PELNUS | Pen en Light for Natural Union of Science, 2025)
The rise of remote work, especially in the post-pandemic era, has significantly transformed workplace dynamics, offering flexibility while also introducing new psychological stressors. This study examines the impact of remote working fatigue on turnover intentions among Millennial employees a demographic known for its adaptability to digital workspaces yet also prone to burnout due to blurred work-life boundaries and increased screen time. Using a quantitative research design, data were collected through a structured survey distributed to Millennial professionals working remotely across various industries. The findings reveal a strong positive correlation between remote working fatigue and the intention to leave one’s job, indicating that sustained fatigue leads to emotional exhaustion and disengagement, ultimately influencing employees’ decisions to resign. This research contributes to the growing body of literature on post-pandemic work models by highlighting the importance of mental health and job satisfaction in virtual environments. The study offers practical recommendations for employers to develop remote work policies that mitigate fatigue, enhance engagement, and support long-term employee retention.